The effect of copper sulfate and zinc oxide in a drench on the gain and health of newly arrived calves - F.K. Brazle; Gerald L. Stokka (Kansas Agricultural Experiment Station Research Reports, 1994)
One hundred and fifty-four, newly arrived, bull calves averaging 295 lb were either drenched with a copper-zinc (Cu-Zn) solution or water at arrival. The Cu-Zn drench did not affect gains during a 56-day trial. Additionally, no differences occurred in morbidity or the number of antibiotic treatments required per animal.
Keywords: Cattlemen' s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Copper; Zinc; Trace minerals